Tinjauan Yuridis Pemenuhan Unsur Pidana Tindakan Terhadap Anak Pelaku Tindak Pidana Penganiayaan Berat (Studi Putusan Nomor 3/PID.SUS-ANAK/2024/PN.MLG) - Ramadhani, Amelia Suci (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
Criminal acts of severe abuse resulting in death may also involve children as perpetrators. In criminal law, children have a special status because they are still in the stage of physical and psychological development, so the juvenile criminal justice system emphasizes educational and rehabilitative punishments. Decision Number 3/Pid.Sus-Anak/2024/PN Mlg shows the application of criminal sanctions against a child who severely abused his classmate, causing death due to bleeding in the dura mater. This study uses a normative juridical approach through case studies, legislation, and conceptual analysis. The application of corrective measures is based on the elements of legal subjects, the prohibition of violence resulting in death, and the principle of the best interests of the child. Corrective measures aim to improve the child's behavior and prevent the recurrence of criminal acts. However, there is still legal ambiguity regarding the age limit of children and the criteria for the severity of criminal acts in the application of corrective measures.